Herbicide selection for wandering Jew (Tradescantia fluminensis) control - Hurrell, G.A.; James, T.K.; Lusk, C.S.; Trolove, M. (New Zealand Plant Protection, 2008)
Wandering Jew (Tradescantia fluminensis) prevents the regeneration of native forests in New Zealand The herbicide triclopyr effectively controls this weed but is damaging to many native plant species To identify alternative herbicides 16 active ingredients representing eight chemical groups were applied to containergrown wandering Jew plants of various ages in three experiments In Experiment 1 triclopyr killed all plants (3 months old) while amitrole caused substantial damage to plants In Experiment 2 amitrole terbuthylazine metsulfuronmethyl and triclopyr provided excellent control of 2 month old plants In Experiment 3 on 4 monthold plants wandering Jew was highly susceptible to triclopyr metsulfuronmethyl fluroxypyr glyphosate fluroxypyr metsulfuronmethyl triclopyr and picloram triclopyr These herbicides were evaluated in a subsequent field trial and all except metsulfuronmethyl gave similar levels of control to Experiment 3 Further investigation of these chemicals is required to determine their optimal use rates and safety for native plants